THE NEXUS OF LANGUAGE AND VALUES: A STUDY OF THE INTEGRATION OF MORAL EDUCATION IN EFL TEXTBOOKS FOR BASIC SCHOOL CURRICULUM IN KURDISTAN - MUSTAFA, SRWA HUSSEIN; HAMAD, KARMAND (Journal of Duhok University, 2023)
English textbooks serve as a crucial element in ELT programs, not only for delivering subject knowledge but also as vehicles for promoting moral and character development. The integration of moral education is globally emphasized due to its potential in enhancing learners’ character, critical thinking, and problem-solving abilities alongside language proficiency attainment. In the specific context of Kurdistan, there is a dearth of research examining the potential of ELT textbooks, while the English textbooks ’Sunrise’ holds a critical position as the primary source of knowledge for learners and teachers. To address this gap, this study adopts a descriptive-analytical methodology, employing content analysis drawing upon Appraisal Theory (AT), guided by a critical pedagogy perspective to explore the representation of moral education content/moral values embedded in the textbooks. Analyzing six textbooks from Primary 4-6 to Secondary 7-9, demonstrates a clear progressive approach, where personal values like a healthy lifestyle, empathy, hygiene, and happiness are initially prioritized, followed by interpersonal values such as caring, politeness, respect, and collaboration. The textbooks also highlight altruistic values related to environmental and global concerns. However, the focus leans towards cultivating good citizenship rather than fostering critical thinking skills and problem-solving ability, prioritizing student behavior over questioning societal values. Further, the study identified the highest coding frequency of four moral education themes in textbooks: Respect for Self and Others, Lack of Prejudice, Appropriate Values and Attitude, and Environment. Overall, the findings reveal that the textbooks primarily emphasize universal moral values, while offering limited representation of Kurdish moral values. This highlights the need for a more comprehensive approach to incorporate moral values in the textbooks’ coverage.